2021
DOI: 10.1111/obr.13296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training before and after bariatric surgery: A systematic review and meta‐analysis

Abstract: We aimed to assess the effectiveness of exercise training programs in adults with severe obesity undergoing bariatric surgery. A systematic search of controlled trials published up to October 2019 that assigned participants to either a preoperative or postoperative exercise training group or a nonexercise group was performed.Meta-analyses were conducted using random-effects models. Twenty-two training programs were assessed (18 performed after bariatric surgery). The effect of preoperative exercise training on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
1
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 70 publications
(279 reference statements)
4
70
1
9
Order By: Relevance
“…(5) smoking [18]; (6) endothelial dysfunction linked with MetS [19], with excessive release of vasoconstrictive agents and defective secretion of smooth-muscle relaxing mediators, such as nitric oxide [20]; (7) gut microbiota dysbiosis connected with MetS [15,[21][22][23]; (8) inflammatory mechanisms, including pro-inflammatory cytokines and chemokines overexpression, cell infiltration and oxidative stress-all induced by excessive immune system stimulation-that are strongly upregulated in the hypertensive setting [24,25]; (9) innate and adaptive immune system involvement [25,26]; (10) nonalcoholic fatty liver disease (NAFLD), also closely associated with MetS [27]; (11) MetS-related brain neurodegenerative disorders, through disruption to the blood-brain barrier, triggering neuroinflammation, and exacerbation of amyloid disorders and decreased function of the cerebral blood vessels, including reduced cerebral blood flow, altered brain autoregulation, and compromised neurovascular coupling [28][29][30][31]; (12) MetS-related cancer development [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) smoking [18]; (6) endothelial dysfunction linked with MetS [19], with excessive release of vasoconstrictive agents and defective secretion of smooth-muscle relaxing mediators, such as nitric oxide [20]; (7) gut microbiota dysbiosis connected with MetS [15,[21][22][23]; (8) inflammatory mechanisms, including pro-inflammatory cytokines and chemokines overexpression, cell infiltration and oxidative stress-all induced by excessive immune system stimulation-that are strongly upregulated in the hypertensive setting [24,25]; (9) innate and adaptive immune system involvement [25,26]; (10) nonalcoholic fatty liver disease (NAFLD), also closely associated with MetS [27]; (11) MetS-related brain neurodegenerative disorders, through disruption to the blood-brain barrier, triggering neuroinflammation, and exacerbation of amyloid disorders and decreased function of the cerebral blood vessels, including reduced cerebral blood flow, altered brain autoregulation, and compromised neurovascular coupling [28][29][30][31]; (12) MetS-related cancer development [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Overstimulated immune system induction of pro -inflammatory cytokines and chemokines overexpression, cell infiltration and oxidative stress [24,25] NAFLD linked with MetS Mainly but not exclusively with hyperinsulinemia-insulin resistance [27] MetS-related brain neurodegenerative disorders Disruption of blood-brain barrier, triggering neuroinflammation and amyloid disorders and decreasing the function of the cerebral blood vessels, including reduced cerebral blood flow, altered brain autoregulation, and compromised neurovascular coupling [28][29][30][31] MetS-related cancer development Arterial hypertension displays a two-fold increased risk for GC development [32,33] MetS, metabolic syndrome; NAFLD, nonalcoholic fatty liver disease; GC, gastric cancer; RAS, renin-angiotensin system; SNS, sympathetic nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported postoperative BS improvements in terms of MS [ 2 , 11 , 13 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] or PF [ 2 , 13 , 26 , 27 , 28 , 30 , 32 , 33 ] after interventions involving isolated aerobic, resistance, or both types of exercise. Strength or PF enhancements have been associated with improved performance of activities of daily living in individuals with obesity [ 34 ] and reduced risk of falls, particularly related to the aging process [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training following RYGB improves MS and physical fitness after BS-induced weight loss [ 13 ]. However, information about these effects in the long term after BS is scarce, since most of the randomized controlled trials in this topic focus on the early postoperative period [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation